Raman spectroscopy of ferromagnetic CrO2 - COEY, JOHN MICHAEL DAVID (American Physical Society, 1999)
Polarized Raman spectra of the ferromagnetic metal CrO2 were measured in a broad temperature range including Tc'390 K. The Raman-allowed modes of A1g , B1g , B2g , and Eg symmetry were identified and compared to the corresponding modes of isostructural TiO2. The two low-frequency Raman lines are relatively narrow, indicating weak scattering of the corresponding B1g and Eg phonons. Whereas the Raman intensities are not visibly affected by the magnetic ordering, the dependences on temperature of the phonon wave numbers exhibit peculiarities that could be attributed to a spin-phonon interaction. The variations with T of the phonon linewidths follow at low temperatures the dependence expected for phonon-phonon scattering. An additional broadening at higher temperatures with a maximum near Tc is tentatively assigned to scattering from collective spin fluctuations.
PUBLISHED
Keywords: Physics